2011
DOI: 10.1080/09540121.2011.554523
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV status to infected children in a Nigerian HIV Care Programme

Abstract: With increasing survival of HIV-infected children, parents face the challenges of disclosure to the children. The aim of this study was to assess the rate of HIV disclosure to children in Ibadan and the factors influencing it in order to guide design of strategies for successful disclosure. A semi-structured questionnaire was administered to consecutive consenting caregivers of HIV-infected children aged ≥6 years attending the Paediatric Infectious Disease Clinic of the University College Hospital, Ibadan, bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
140
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(173 citation statements)
references
References 16 publications
28
140
4
1
Order By: Relevance
“…A total of 31 (33.0%) of HIV infected children studied had a form of information about their status. This is higher than 13.0% reported by Brown et al 15 in a study in Ibadan, southwest, Nigeria but consistent with a later study carried out by Ubesie et al 17 (29.0%). This suggests an increase in enlightenment and awareness of the need of disclosing HIV status to infected children.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A total of 31 (33.0%) of HIV infected children studied had a form of information about their status. This is higher than 13.0% reported by Brown et al 15 in a study in Ibadan, southwest, Nigeria but consistent with a later study carried out by Ubesie et al 17 (29.0%). This suggests an increase in enlightenment and awareness of the need of disclosing HIV status to infected children.…”
Section: Discussioncontrasting
confidence: 47%
“…Vreemanet al 12 reported level of status disclosure to be between 0 to 69.2%. Mialky et al 14 reported 43% disclosure rate with mean age of nine years, 23% of them have disclosed status to school authority, while Brown et al 15 in a study in Nigeria reported a lower level of status disclosure (13.0%). Common barriers to status disclosure in the review by Vreeman et al 12 were fear that the child would disclose HIV status to others, fear of stigma and concerns of emotional and physical health of child.…”
Section: Introductionmentioning
confidence: 99%
“…ART adherence has been shown to increase following full disclosure (Bikaako-Kajura et al, 2006;Brown et al, 2011;Fetzer et al, 2011;Hejoaka, 2009;Vaz et al, 2008) with improvements in CD4 counts leading to fewer incidences of disease progression and death (Enzama & Mugyenyi, 2005;Ferris et al, 2007). HCPs should encourage parents of infected children with deteriorating health status and reducing CD4 counts to perform full disclosure to these children.…”
Section: Discussionmentioning
confidence: 99%
“…HIV disclosure studies in SSA have mainly centered on telling children about their own HIV status, and a few have been on telling children about their parents" HIV statuses. Recent studies on disclosure to HIV-positive children have revealed HIV disclosure rates between 2-50% in Kenya (John-Stewart et al, 2013;Turissini et al, 2013;Vreeman et al, 2010;Vreeman et al, 2014); and 2-38% in other SSA countries (Biadgilign et al, 2011;Bikaako-Kajura et al, 2006;Brown et al, 2011;Feinstein et al, 2010;Fetzer et al, 2011;Hejoaka, 2009;Kallem et al, 2011, Menon et al, 2007Moodley et al, 2006;Vaz et al, 2010). Research suggests that the typical age ranges of HIV-positive children receiving disclosure of their own HIV status was between 3 and 19 years in Kenya (Vreeman et al, 2014); 8 and 18 years in the Democratic Republic of Congo (Vaz et al, 2010;Vaz et al, 2008); and 5 and 15 years in South Africa (Heeren et al, 2012;Moodley et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This is more so when there are many family members infected, who may include both parents (Republic of Kenya, 2009). When parents delay disclosure, children sense secrets within their households and ask persistent questions in a bid to elicit disclosure (Brown et al, 2011;Gachanja, 2015;Gachanja et al, 2014a;Gachanja et al, 2014b;Kallem et al, 2011;Kouyoumdjian et al, 2005;Petersen et al, 2010;Vaz, Maman, Eng, Barbarin, Tshikandu, & Behets, 2011). Disclosure is a process that moves children from a state where they have no disclosure or no knowledge of their parents' illnesses (Bikaako-Kajura et al, 2006;Kallem et al, 2011;Oberdorfer et al, 2006;Vaz et al, 2011), to partial disclosure where they know that their parents have a chronic illness or are taking medications (Bikaako-Kajura et al, 2006;Rochat, Mkwanazi, & Bland, 2013;Vaz et al, 2011), and finally to full disclosure when the children are told that their parents are infected with HIV (BikaakoKajura et al, 2006;Kallem et al, 2011;Oberdorfer et al, 2006;Rochat et al, 2013).…”
Section: Introductionmentioning
confidence: 99%